1998
DOI: 10.1111/j.1469-7793.1998.917bd.x
|View full text |Cite
|
Sign up to set email alerts
|

The compliance of the porcine pulmonary artery depends on pressure and heart rate

Abstract: Pulmonary flow can be derived from a pulmonary arterial pressure curve for patients for which this pressure is routinely determined, such as patients who are undergoing intensive care, cardio-thoracic surgery or a catheterization for diagnostic reasons, without the use of a flow probe. To compute the pulmonary blood flow beat-to-beat for a specific haemodynamic condition from the arterial pressure curve a windkessel model should be used. To do so, the dynamic compliance of the pulmonary artery under the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Pressure dependence of vascular compliance agrees with earlier findings on the pulmonary artery (7,16) and the aorta (17,19,22). Several models to describe the relationship between pressure and compliance have been proposed in the literature (16,17,19,22), most of them being exponential. When fitted to the data, the model of Fung (43) showed that the term in the denominator is negligible, and thus the inverse model presented above suffices.…”
Section: Discussionsupporting
confidence: 89%
“…Pressure dependence of vascular compliance agrees with earlier findings on the pulmonary artery (7,16) and the aorta (17,19,22). Several models to describe the relationship between pressure and compliance have been proposed in the literature (16,17,19,22), most of them being exponential. When fitted to the data, the model of Fung (43) showed that the term in the denominator is negligible, and thus the inverse model presented above suffices.…”
Section: Discussionsupporting
confidence: 89%
“…Another mechanism that may have contributed to the proportionately greater reduction in C PA in healthy controls may be the higher exercise‐induced increase in heart rate. It has been shown for both the systemic and the pulmonary circulation that an increase in heart rate is associated with a reduction in arterial compliance . Thus, the change in C PA during exercise per se cannot be used to distinguish between a normal and abnormal pulmonary vascular reserve.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown for both the systemic and the pulmonary circulation that an increase in heart rate is associated with a reduction in arterial compliance. 31,32 Thus, the change in C PA during exercise per se cannot be used to distinguish between a normal and abnormal pulmonary vascular reserve. Nevertheless, whereas controls demonstrated the greatest reductions in C PA during exercise, peak exercise values still remained higher than the resting values in CTEPH and post-PEA patients.…”
Section: Pulmonary Arterial Compliance Decreases During Exercisementioning
confidence: 99%
“…In a simplified scheme, τ can be considered to be the product of the total vascular resistance ( R P ) and the overall compliance ( C T ) of the arterial tree, the so‐called total arterial compliance. Its applicability and limitations in systemic and pulmonary circuits have been discussed (Kornet et al. 1985, Levy et al.…”
Section: Discussionmentioning
confidence: 99%